External beam radiation therapy as an alternative to brachytherapy for locally advanced cervical cancer - Zh. A. Startseva; P. A. Lushnikova; E. S. Sukhikh (Сибирский онкологический журнал)
The purpose of the study was to analyze and summarize the available literature data on the potential value of radiation therapy for locally advanced cervical cancer and to present alternative treatment options when conventional treatment is not feasible. Material and Methods. A literature search was conducted using PubMed and Cochrane Library databases as well as databases of clinical materials from the Ministry of Health of the Russian Federation, ASCO (American Society of Clinical Oncology), and National Comprehensive Cancer Network (NCCN). Literature sources and publications from 2004 to 2021 were included into the review. Results. The review outlines the basic principles of classical treatment of locally advanced cervical cancer (external beam radiation therapy followed by brachytherapy boost). Alternative treatment options for patients not eligible for brachytherapy have been shown. Methods of using stereotactic treatment as an alternative to brachytherapy have been described. The results of researches who applied a new treatment method, namely, two-stage stereotactic body radiation therapy for patients with locally advanced cervical cancer have been demonstrated. Conclusion. The use of modern devices for radiation therapy, such as the linear electron accelerator and modern planning stations for medical physicists, may make it possible to use a new option in the treatment of patients with locally advanced cervical cancer – the use of stereotactic boost. This issue is still controversial and requires further study.